Human Resources Management in Project Success at the Saudi Basic Industries Corporation (SABIC) (The International Journal for Scientific Research, 2024)
The focus of the study is to explain the role of human resources management in the success of projects in the Saudi Basic Industries Corporation (SABIC) in the Kingdom of Saudi Arabia. The descriptive analytical application was used using the questionnaire study tool for a direct sample of 100 employees in the most important results: There is a relationship that has proven successful in human resources management to achieve the success of projects in the Saudi Basic Industries Corporation (SABIC) in the Kingdom of Saudi Arabia, There is a positive relationship in human resources management to achieving success in projects in the Saudi Basic Industries Corporation (SABIC) in the Kingdom of Saudi Arabia, After managing human resources in discussions and meetings related to senior levels.
Keywords: Human Resources Management; Project Success; Saudi Basic Industries Corporation